GENDER DIFFERENCES AMONG MOG PLAYERS IN THEIR SOCIALISATION PROCESSES - Casañ-Pitarch, Ricardo (Advanced Education, 2018)
The increasing popularity of multiplayer online video games has given rise to the creation of linguistic communities with specific forms of communication and rules. Among the several features of those digital communities, some differences among men’s and women’s communication behaviours seem to be real when they play video games. Thus, the objective of this research is to analyse gender differences in the socialisation process among MOG Players (Multiplayer Online Game). To this aim, this research introduces an experiment with 201 MOG players (males: 147; females: 54) who responded to a survey concerning the use of 20 social communicative acts (based on Guntermann and June, 1982, p. 26) in three different contexts: the participant knew in advance the other player from a) the real world, b) the virtual world, or c) they had never met before. The results obtained from this analysis have shown some differences between both male and female MOG participants in their socialisation process when interacting with other players by determining the frequency and the per cent variation on the use of the selected communicative acts. In conclusion, it seems that there are some similarities and differences between men and women when interacting with MOG players that may interfere in the way they play videogames and behave towards other players.